2014
DOI: 10.3126/jkmc.v3i2.11228
|View full text |Cite
|
Sign up to set email alerts
|

Double J stenting compared with ureteral catheterization in percutaneous Nephrolithotomy

Abstract: Background: Nephrolithiasis represents a large portion in the fi eld of Urological pathology. Minimal invasive and non-invasive therapies have become more accessible and effi cient in the treatment of nephrolithiasis. Percutaneous nephrolithotomy (PCNL) is an effective minimal invasive modality of treating kidney stones. Objectives: To evaluate the outcome of standard percutaneous nephrolithotomy (PCNL) using two different stenting techniques i.e. externalized ureteral catheter placement compared with Double-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…p=0.931), and length of hospital stay (5.70±2.72 days vs. 5.72±2.08 days, p=0.961) in both the groups [ 11 ]. Joshi et al in another similar study evaluated the outcome of standard PCNL using two different stenting techniques, i.e., externalized ureteral catheter placement compared with double-J stent placement and reported that 64% of patients showed stent-related symptoms in the double-J stenting group, while in the EUC group, 28% of patients experienced such complications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…p=0.931), and length of hospital stay (5.70±2.72 days vs. 5.72±2.08 days, p=0.961) in both the groups [ 11 ]. Joshi et al in another similar study evaluated the outcome of standard PCNL using two different stenting techniques, i.e., externalized ureteral catheter placement compared with double-J stent placement and reported that 64% of patients showed stent-related symptoms in the double-J stenting group, while in the EUC group, 28% of patients experienced such complications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%